Hanging Green Space: Assessing the Relationship between Students' Horticultural Involvement and Environmental Awareness - Mellona, Jonathan P.; Peria, Jo Neil (Future Science / FSH-PH Publications, 2025)
The world is experiencing various environmental issues which pose serious threat to human health and well-being. These problems must be introduced to the classroom to raise environmental awareness among the students. In relation to the strategies in teaching environmental education, schools utilize gardens to provide students with hands-on learning. This study aimed to determine the relationship between Grade 11 STEM students’ horticultural involvement and their environmental awareness through Hanging Green Space Project at Pasig National High School during the second semester of the school year 2024-2025. The study employed descriptive correlational research design and gathered data from selected 81 Grade 11 STEM students through survey questionnaires. Descriptive statistics revealed that students strongly agreed on their active involvement in horticulture and demonstrated high levels of environmental awareness after conducting the Hanging Green Space Project. Meanwhile, inferential statistics using Pearson’s correlation showed a significant relationship between students’ horticultural involvement and environmental awareness, correlation values ranging from 0.221 to 0.371 (p<0.05), indicating weak to moderate positive relationship. These results imply that students who are actively engaged in horticultural activities tend to be more aware of the environmental issues. Furthermore, the study recommends incorporating horticultural or gardening activities various discipline to connect the practical activities with theoretical and ethical reflections. In addition, incorporating gardening into a broader curriculum framework is encouraged to sustain development of horticultural involvement and promote awareness of environmental issues among wider groups of learners.